Evidence for a conserved CCAP-signaling pathway controlling ecdysis in a hemimetabolous insect, Rhodnius prolixus - Lee, Do Hee; Orchard, Ian; Lange, Angela B. (Frontiers in Neuroscience, 2013)
A vital feature in the success of Ecdysozoa is their ability to shed their exoskeleton (a process called ecdysis) such that they can grow or change their morphology. In holometabolous insects, these behaviours are orchestrated by the sequential actions of neuropeptides, one of which is crustacean cardioactive peptide (CCAP). Little is known about the control of ecdysis in hemimetabolous insects. Here, we report that CCAP is essential for successful ecdysis in the hemimetabolous insect, Rhodnius prolixus; the vector of Chagas disease. The first indication of CCAP’s involvement in ecdysis was the observation of decreased staining intensity of CCAP-containing neurons immediately following ecdysis, indicative of the release of CCAP. The critical importance of the CCAP signaling pathway was further demonstrated by knockdown (as determined by qPCR and immunohistochemistry) of the CCAP and CCAPR transcripts utilizing dsRNA. This technique reduced the staining intensity of CCAP-containing neurons, and knocked down the transcript levels by up to 92%, with lethal consequences to the insect. Insects with these transcripts knocked down had very high mortality (up to 84%), typically at the expected time of the ecdysis sequence, or had ecdysis extremely delayed. This is the first report of the susceptibility of R. prolixus to dsRNA knockdown of neuropeptide and receptor transcripts, and the data clearly demonstrates the conserved nature of the CCAP signaling pathway in ecdysis between holometabolous and hemimetabolous insects.